Dual Delay-Compensation-Based Model Predictive Control for the Semi-Controlled Open-Winding PMSM System - Zhang, Xiaoguang; Wang, Keqin; Zhang, Wenhan; Wang, Yaoqiang; Wang, Peng; Gao, Dawei (IEEE access, 2019)
To improve the control performance of the semi-controlled open-end winding permanent magnetic synchronous motor (SOEW-PMSM) control system, a novel prediction control method is presented in this paper. First, the current-voltage dual delay-compensation algorithm is presented to overcome the negative influence on the steady-state performance of the whole control system. Then, in order to implement the simultaneous control of the d-axis current, the q-axis current, and the zero-sequence current, the current-error-based cost function is designed. Additionally, to further improve the control performance and decrease the calculation complexity of the prediction algorithm, controllable converter vector optimization-based prediction control method is presented. The effectiveness of the proposed prediction methods is tested by the simulation and experimental results.